Microstructure and properties of silver based cadmium free electrical contact materials - Talijan N.; Ćosović V.; Stajić-Trošić Jasna; Grujić A.; Živković Dragana; Romhanji E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The presented work covers part of experimental results of simultaneous study of microstructure, density, hardness and electrical conductivity of sintered electrical contact materials based of Ag- SnO2 with 8, 10 and 12 mass% SnO2. The mentioned characteristics were analyzed in the function of different sintering regimes and after additional mechanical treatment (forging and rolling). The influence of small addition of In2O3 (2.9 mass%) on the increase of dispersion of main oxide SnO2 in Ag matrix is observed and presented also.